THE EFFECT OF COMPENSATION ON EMPLOYEE SATISFACTION AT UUO KUD SAWIT JAYA BANGKINANG DISTRICT - Septian Dwi Azhari; Suarni Norawati; Adi Setiawan (STIE Bangkinang Publishing, 2021)
This study aims to determine the effect of compensation on employee job satisfaction at UUO KUD Sawit Jaya, Bangkinang District. The sample of this study used a saturated sampling technique (census), namely 49 employees at UUO KUD Sawit Jaya, Bangkinang District. The data collection techniques used were questionnaires and research files. The data analysis technique used is simple regression analysis with a significant level (α) of 0.05. The results of this study conclude that compensation has a significant effect on employee job satisfaction, with a significant value less than 0.05. The contribution of the independent variable to the dependent variable is strong.